Bone loss over 1 year of training and competition in female cyclists - Sherk, V. D.; Barry, D. W.; Villalon, K. L.; Hansen, K. C.; Wolfe, P.; Kohrt, W. M. (Clinical Journal of Sport Medicine, 2014)
Objective: To observe changes in hip, spine, and tibia bone characteristics in female cyclists over the course of 1 year of training.